Near-Infrared Light-Mediated Nanoplatforms for Cancer Thermo-Chemotherapy and Optical Imaging - Zhang, Zhenjiang; Wang, Jing; Chen, Chunying (Advanced materials (Weinheim), 2013)
While thermo‐chemotherapy has proved to be effective in optimizing the efficacies of cancer treatments, traditional chemotherapy is subject to adverse side effects and heat delivery is often challenging in operation. Some photothermal inorganic nanoparticles responsive to near infrared light provide new opportunities for simultaneous and targeted delivery of heat and chemotherapeutics to the tumor sites in pursuit of synergistic effects for efficacy enhancement. The state of the art of nanoparticle‐induced thermo‐chemotherapy is summarized and the advantages and challenges of the major nanoplatforms based on gold nanoparticles, carbon nanomaterials, palladium nanosheets, and copper‐based nanocrystals are highlighted. In addition, the optical‐imaging potentials of the nanoplatforms that may endow them with imaging‐guided therapy and therapeutic‐result‐monitoring capabilities are also briefly discussed. Photothermal inorganic nanoparticles responsive to near infrared light provide new opportunities for simultaneous targeted delivery of heat and chemotherapeutics to tumors in pursuit of synergistic effects for efficacy enhancement. The state of the art in nanoparticle‐induced thermo‐chemotherapy and optical imaging is summarized, and the major nanoplatforms based on gold nanoparticles, carbon nanomaterials, palladium nanosheets, and copper‐based nanocrystals are discussed.